Aberrant upregulation of PDK1 in ovarian cancer cells impairs CD8+ T cell function and survival through elevation of PD-L1. (2nd November 2019) - Wang, Jing-Jing; Siu, Michelle K.; Jiang, Yu-Xin; Leung, Thomas H.; Chan, David W.; Cheng, Ran-Ran; Cheung, Annie N.; Ngan, Hextan Y.; Chan, Karen K.
ABSTRACT: Blockade of the programmed cell death 1(PD-1)/PD-1 ligand-1(PD-L1) pathway has been exploited therapeutically in many cancer types. Upregulation of PD-L1 in tumor cells contributes to malignancy through suppression of the T cell-mediated antitumor response. Pyruvate dehydrogenase kinase 1 (PDK1), a glycolytic gate-keeping enzyme, is also known to promote tumor development. Here, we have uncovered a mechanism of regulation of PD-L1 by PDK1 through activation of c-Jun-NH2 -kinase (JNK)-c-Jun in ovarian cancer cells. Elevated PDK1 expression was correlated with that of PD-L1 in the TCGA ovarian cancer dataset and ovarian cancer tissue array. Overexpression of PDK1 in ovarian cancer cells impaired CD8 + T cell function by suppressing IFN-γ secretion through the PD-1/PD-L1 pathway. Conversely, knockdown of PDK1 in ovarian cancer cells relieved suppression of CD8 + T cell function. CD8 + T cell apoptosis induced by binding of PD-1 with PD-L1 was increased after co-culture with ovarian cancer cells overexpressing PDK1, while depletion of PDK1 exerted the opposite effect. In vivo experiments revealed synergistic improved overall survival and enhanced inhibition of tumor growth upon co-treatment with dichloroacetate (DCA), a PDK inhibitor, and PD-L1 antibody, accompanied by increased IFN-γ secretion by monocytes infiltrating tumor islets. Moreover, PDK1 expression and CD8 + T cell infiltration were inversely correlated in the ovarian cancer tissue array. Our collective findings provide a novel explanation of how PDK1 contributes to upregulation of PD-L1 in ovarian cancer and highlight its potential as a target therapeutic molecule that cooperates with the immune checkpoint blockade.